Effect of Virtual Reality (VR)–Based Learning Media on Grade XI Students’ Learning Outcomes in the Human Respiratory System - Indriyani, Nova; Dimenta, Rivo Hasper; Sari, Novi Fitriandika (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine the effect of Virtual Reality (VR)-based instructional media on students’ learning outcomes in the respiratory system topic among Grade XI students at SMA Has Sepakat. A quantitative approach was employed using a quasi-experimental pretest–posttest control group design. The study involved 40 students, comprising 20 students in the experimental group and 20 students in the control group, selected through cluster random sampling. The experimental group received instruction using three-dimensional VR simulations that visualized respiratory organ structures, inspiration–expiration mechanisms, and gas exchange processes, whereas the control group received conventional instruction. Data were collected using a validated and reliable multiple-choice achievement test. Statistical analyses were performed using an independent-samples t-test and effect size calculation with SPSS version 22. The mean pretest score was 30.90 in the control group (SD = 9.049; 95% CI = 26.66–35.14) and 25.40 in the experimental group (SD = 8.708; 95% CI = 21.32–29.48). After the intervention, the mean posttest score increased to 60.00 in the control group (SD = 15.681; 95% CI = 52.66–67.34) and 77.80 in the experimental group (SD = 12.068; 95% CI = 72.15–83.45). The independent-samples t-test indicated a significant difference in posttest learning outcomes between the two groups (t = −4.023, p < 0.001), with a mean difference of −17.800. The effect size was 1.27, indicating a large difference between the groups. These findings suggest that VR-based instruction was associated with higher learning outcomes in the respiratory system topic. However, the results should be interpreted cautiously because the two groups differed in their initial pretest performance.